2022
DOI: 10.3390/cancers14061368
|View full text |Cite
|
Sign up to set email alerts
|

Functional Decline in the Cancer Patient: A Review

Abstract: A decline in functional status, an individual’s ability to perform the normal activities required to maintain adequate health and meet basic needs, is part of normal ageing. Functional decline, however, appears to be accelerated in older patients with cancer. Such decline can occur as a result of a cancer itself, cancer treatment-related factors, or a combination of the two. The accelerated decline in function seen in older patients with cancer can be slowed, or even partly mitigated through routine assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 134 publications
2
30
0
Order By: Relevance
“…Non-small cell lung cancer (NSCLC) is the leading cause of cancerrelated death in the US with 68% of cases diagnosed in adults age ≥ 65 [1]. Older adults who receive systemic therapy are at risk for impaired physical function from both the cancer and the treatment [2][3][4][5][6][7], and functional decline is associated with worse quality of life and survival [2,8,9]. In a study of older adults, >70% of those with cancer reported that they would not select a treatment that caused severe functional impairment, even if it improved survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the leading cause of cancerrelated death in the US with 68% of cases diagnosed in adults age ≥ 65 [1]. Older adults who receive systemic therapy are at risk for impaired physical function from both the cancer and the treatment [2][3][4][5][6][7], and functional decline is associated with worse quality of life and survival [2,8,9]. In a study of older adults, >70% of those with cancer reported that they would not select a treatment that caused severe functional impairment, even if it improved survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…While rates are higher during treatment and for patients with metastatic disease, a recent meta-analysis reported a pain prevalence rate of 39.3% among post-treatment cancer survivors [ 37 ]. Pain is a well-known predictor of functional impairment and decline among older cancer survivors [ 38 , 39 , 40 ], so it is not surprising that it was associated with worse physical function during the study. This study did not assess whether pain management changed during the study, but some studies have reported reduced outpatient healthcare visits during the early stages of the pandemic [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, depression in cancer survivors appears to be underdiagnosed and untreated [ 49 ]. Fatigue and depression also are well-known predictors of physical function decline among older cancer survivors [ 38 , 39 , 40 ]. There have been fewer studies examining the association between sleep disturbance and impaired physical functioning among cancer survivors, but evidence to date suggests that sleep disturbance is associated with problems with instrumental activities of daily living (IADLs) or poor self-reported physical function [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While, the management strategies of functional decline largely overlap with those targeting frailty, given that frailty is effectively a marker for the potential for functional decline. 56 So, reversing the frailty may play an important role in improving functional status. In addition, early detection, physical activity, and dietary interventions should also be helpful.…”
Section: Discussionmentioning
confidence: 99%